Hermeneutika Maqāṣidī Imam al-Shāṭibī - Adang Saputra (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
Al-Syāṭibī is one of the scholars who have innovative thought on Qur’anic hermeneutics in the classical Muslim scholarship. He was proposed a “reading based on maqāṣīd” on the shari’a which differed from that of earlier methods. Marginally, Al-Syāṭibī’s hermeneutic abbreviation comprised of three tenets: (1) accentuating Arabic aspect as foothold in interpretation process on the shari’a, (2) emphasizing reading base on maqasid through circular-relational study on text-author-reader and other various accompaniment indicators, and (3) acknowledging reader circumstance role in the process of interpretation, so that no single-objective truth in interpretation.